Analysis and design of marine structures - Soares, C. Guedes; Romanoff, Jani (CRC Press, 2013)
Analysis and Design of Marine Structures includes the papers from MARSTRUCT 2013, the 4th International Conference on Marine Structures (Espoo, Finland, 25-27 March 2013). The MARSTRUCT series of conferences started in Glasgow, UK in 2007, followed by the second conference in Lisbon, Portugal (March 2009), while the third conference was held in Hamburg, Germany (March 2011). All MARSTRUCT-conferences deal with Ship and Offshore Structures, whereby this present volume focusses on:- Methods and Tools for Loads and Load Effects; - Methods and Tools for Strength Assessment; - Experimental Analysis.